Quantitative Analysis of Cepharanthine in Plasma Based on Semiautomatic Microextraction by Packed Sorbent Combined with Liquid Chromatography - Camille Desgrouas; Marc Desbordes; Jérôme Dormoi; Evelyne Ollivier; Daniel Parzy; Nicolas Taudon (Journal of Analytical Methods in Chemistry)
The spread of Plasmodium falciparum resistance toward most of the used drugs requires new antimalarial compounds. Taking advantage of the biodiversity, the ethnopharmacological approach opens the way for the discovery and the characterization of potent original molecules. Previous works led to the selection of a bisbenzylisoquinoline, cepharanthine, extracted from Stephania rotunda, which is mainly present in Cambodia. A sensitive and selective liquid chromatography method has been developed for the determination of cepharanthine in mouse plasma. The method involved a semiautomated microextraction by packed sorbent (MEPS) using 4 mg of solid phase silica-C8 sorbent. LC separation was performed on a Kinetex XB-C18 column (2.6 µm) with a mobile phase of acetonitrile containing formic acid and 10 mM ammonium formate buffer pH 3.5. Data were acquired at 282 nm with a diode array detector. The drug/internal standard peak area ratios were linked via linear relationships to plasma concentrations (75–2,000 ng/mL). Precision was below 5% and accuracy was 99.0–102%. Extraction recovery of cepharanthine was 56–58%. The method was successfully used to determine the pharmacokinetic profile of cepharanthine in healthy and Plasmodium berghei infected mice. The infection did not impact pharmacokinetic parameters of cepharanthine.